Manejo y complicaciones de fracturas expuestas por proyectil de arma de fuego artesanal (armadillo) en pacientes atendidos en el servicio de traumatología - Hospital Regional de Loreto. Julio 2018 a julio 2019 - Davila Andi, Jack Fabricio (2021)
The exposed fractures produced by artisanal firearm projectiles, known as “tramperas” or “Armadillo” in the Loreto region, in recent years are a common denominator in the majority of hospital admissions due to complex musculoskeletal injuries, of long hospital stay and complications that leave considerable sequelae. The exposed fractures produced by these arms are a challenge for the orthopedic surgeon, they appear especially in the season of emptying of the rivers. There are no records or documented studies on this issue in Peru, even less in the Loreto Region, where many cases occur, so it is important to know this problem through a research study to determine the appropriate and timely management, as well as the potential complications of the accident, associating the clinical characteristics with morbidity and mortality, during the treatment and management of the injuries. For these reasons, the following question is formulated, what is the management and complications of fractures exposed by a projectile of a handmade firearm (armadillo) in patients treated in the trauma service - regional hospital of Loreto, July 2018 - July 2019? The study design will be non-experimental, cross-sectional, retrospective analysis with a review of the medical records of all patients diagnosed with fracture exposed by artisanal firearm projectile (armadillo), treated in the trauma service of the Regional Hospital of Loreto during the period July 2018 to July 2019.